2022
DOI: 10.1021/acs.nanolett.2c00917
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Cytosolic Stability of Small DNA Nanostructures In Cellula

Abstract: DNA nanostructures have proven potential in biomedicine. However, their intracellular interactionsespecially cytosolic stabilityremain mostly unknown and attempts to discern this are confounded by the complexities of endocytic uptake and entrapment. Here, we bypass the endocytic uptake and evaluate the DNA structural stability directly in live cells. Commonly used DNA structurescrosshairs and a tetrahedronwere labeled with a multistep Förster resonance energy transfer dye cascade and microinjected into th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 46 publications
(104 reference statements)
3
15
0
Order By: Relevance
“…Results, summarized in Figure e, show that PB NPs remained stable regardless of the scaffold used for their assembly. Previous studies on the cytosolic stability of polyhedral DNA-NPs as well as in the cell lysate agree with these results …”
Section: Resultssupporting
confidence: 89%
“…Results, summarized in Figure e, show that PB NPs remained stable regardless of the scaffold used for their assembly. Previous studies on the cytosolic stability of polyhedral DNA-NPs as well as in the cell lysate agree with these results …”
Section: Resultssupporting
confidence: 89%
“…3 shows results from a recent report where dye-labeled DNA structures were directly microinjected into the cytosol of a variety of different primary and transformed cells and the stability of the structures evaluated by tracking the resulting FRET over time. 86 This format was exploited to bypass the complications of endocytic uptake so that the only variable became that of cytosolic stability. This study confirmed that the high-torsion DNA tetrahedron is more stable in the cellular cytosol than linear structures.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…Furthermore, expanding cytosolic studies to other DNA NS types as well as integration of stabilizing techniques are needed. 86…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] This surge in popularity can be attributed to the programmability and precise control over the size, shape, function, and biocompatibility of these structures. FNAs have been shown to maintain their structural stability and integrity in biological fluids, [11][12] and can be effectively internalized by mammalian cells without the transfectants or transfection methods. [13] Much work has been done to explore the mechanisms of the cellular uptake of DNA nanostructures.…”
Section: Introductionmentioning
confidence: 99%